Endometrial Cancer Ameliorating Effect of Momordica charantia Extract Through Bitter Taste Receptors - Hiramoto, Keiichi; Oikawa, Hirotaka (Discoveries in Agriculture and Food Sciences, 2025)
Momordica charantia (MC) extract contains various bitter components. These bitter components exert anticancer effects. However, the impact of MC extract on endometrial cancer remains unknown. In this study, we analyzed the effects of the MC extract on endometrial cancer induced by N-methyl-N-nitrosourea (MNU) and estradiol, as well as its relationship with bitter taste receptors. After cancer induction in mice, they were administered MC extract (50 mg/kg) or the bitter receptor antagonist 6-methoxyflavone (6-MOF; 50 mg/kg), three times weekly during the experimental period. The treatment with MC extract alleviated endometrial cancer symptoms, whereas, 6-MOF administration worsened them. MC extract enhanced intrauterine expression of the bitter taste receptor and remained unchanged by the 6-MOF treatment. MC extract treatment increased the abundance of this bitter taste receptor on macrophages and mast cells, whereas, their abundance was elevated in neutrophils after 6-MOF treatment. Furthermore, the cancer-associated increase in the frequency of myofibroblasts was significantly suppressed after MC extract treatment and enhanced by 6-MOF. Our results demonstrate the MC extract-induced alleviation of endometrial cancer, which was aggravated by 6-MOF treatment. We propose the regulation of this phenomenon through a signaling pathway mediated by bitter taste receptors.